Aluminum nitride ceramic for electronic packaging and preparation method thereof

By using erbium hydride and yttrium oxide as composite sintering additives during the sintering process of aluminum nitride ceramics, the problems of limited densification effect of a single sintering additive and difficulty in removing grain boundary phases are solved, and aluminium nitride ceramic materials with high density and high thermal conductivity are achieved.

CN118930279BActive Publication Date: 2025-04-08WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411218058.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-04-08
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing aluminum nitride ceramics use a single sintering additive during the sintering process, resulting in limited densification effect and difficulty in removing residual grain boundary phases, resulting in a degradation of overall performance.

Method used

Erbium hydride and yttrium oxide are used as composite sintering aids to promote densification by generating liquid phases, and reduce the grain boundary phase content through volatility of Erbium aluminate, thereby improving the thermal conductivity of the sintered body.

Benefits of technology

It significantly improves the density and thermal conductivity of aluminum nitride ceramics, reduces grain boundary phase content, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention proposes an aluminum nitride ceramic for electronic packaging and a preparation method thereof, which belongs to the field of electronic packaging ceramic materials. In the sintering process of the aluminum nitride ceramic, aluminum nitride is used as a raw material, and erbium hydride and yttrium oxide are added as composite additives for sintering. The erbium hydride powder and yttrium oxide powder are 1wt% to 5wt% of the total mass of the mixed material required for sintering according to the mass percentage, and the balance is aluminum nitride powder. The present invention adopts rare earth hydride as a sintering additive. The rare earth element single substance generated by the decomposition of the hydride can combine with the oxygen element in the aluminum oxide, and the generated rare earth oxide can continue to react with the aluminum oxide. The rare earth hydride has a dual deoxidation effect, which prevents oxygen from entering the aluminum nitride lattice to form defects, and can effectively improve the thermal conductivity; using erbium hydride and yttrium oxide as composite sintering additives can reduce the eutectic line of the aluminate liquid phase, so that the liquid phase appears at a lower temperature, and promotes the density of the sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic packaging materials, and in particular to an aluminum nitride ceramic for electronic packaging and a preparation method thereof. Background Art

[0002] In recent years, aluminum nitride ceramics have been widely used due to their high thermal conductivity, low dielectric constant, low dielectric loss, linear expansion coefficient matching that of semiconductor materials such as silicon, high insulation, and high mechanical strength (the theoretical thermal conductivity of aluminum nitride single crystal at room temperature is 320W / (m·K), which is more than 5 times that of aluminum oxide; the band gap is 6.2eV, which is a good insulator; the linear expansion coefficient is 3.5×10 -6 K -1 ) and has become the first choice for insulating heat dissipation packaging materials and semiconductor substrate materials. It is widely used in electronics, automobiles, aerospace, military and other fields. However, aluminum nitride is difficult to sinter densely because it is a strong covalent compound with a small self-diffusion coefficient and a high melting point. At the same time, due to the presence of the surface oxide film, oxygen atoms are easily dissolved into the aluminum nitride lattice and produce aluminum vacancies, which intensifies phonon scattering and reduces the thermal conductivity of aluminum nitride.

[0003] It is well known that adding sintering aids during sintering of aluminum nitride ceramics can effectively improve the sintering performance. At present, the widely used additives are rare earth or alkaline earth oxides and fluorides (such as Y2O3, YF3, CaO, CaF2, etc.). The low-melting-point sintering aids themselves melt to produce a liquid phase or react with the aluminum oxide on the surface of aluminum nitride to produce a liquid phase, which accelerates mass transfer, thereby reducing the temperature required for densification and purifying the aluminum nitride lattice. However, a single sintering aid has limited effect on promoting densification, and since the residual grain boundary phase generated is difficult to remove, these problems will lead to a decrease in the overall performance of aluminum nitride ceramics. Composite sintering aids can reduce the eutectic line of the aluminate liquid phase, make the liquid phase appear at a lower temperature, and promote the density of the sample. The erbium element decomposed by erbium hydride at high temperature reacts with aluminum oxide to generate erbium oxide, and the erbium oxide further reacts with aluminum oxide to generate erbium aluminate. Since the saturated vapor pressure of the generated erbium aluminate is relatively high, the erbium aluminate grain boundary phase in aluminum nitride is easily volatilized at high temperature, thereby reducing the grain boundary phase content. Compared with the currently widely used sintering system, the present invention aims to use a novel composite auxiliary agent system composed of rare earth hydride and rare earth oxide, namely erbium hydride and yttrium oxide, to reduce the sintering temperature of the product, improve the microstructure, and increase the densification and thermal conductivity. Summary of the invention

[0004] In view of this, the present invention proposes an aluminum nitride ceramic for electronic packaging and a preparation method thereof, which is used to solve the problem that the current single sintering aid has limited effect on promoting densification, and the residual grain boundary phase generated is difficult to remove, which will lead to a decrease in the overall performance of the aluminum nitride ceramic.

[0005] The technical solution of the present invention is implemented as follows: The present invention provides a method for preparing aluminum nitride ceramics for electronic packaging. During the sintering process of aluminum nitride ceramics, aluminum nitride is used as a raw material, and erbium hydride and yttrium oxide are added as composite additives for sintering. The mass percentage of erbium hydride powder and yttrium oxide powder is 1wt%~5wt% of the total mass of the mixed material required for sintering.

[0006] The core principle of the present invention is that the composite sintering aid can more effectively promote the generation of the liquid phase than a single aid. The generated liquid phase will preferentially occupy the position with the lowest free energy and flow in the capillary direction with the highest energy per unit volume. When the liquid phase is not enough to fill all the pores, the liquid phase will try to pull the solid particles together through capillary forces to reduce the overall free energy, thereby significantly improving the densification of the material. In addition, the generation of the liquid phase causes the surface layer of the aluminum nitride grains to dissolve in the liquid phase and re-precipitate in the subsequent process. In this dissolution-precipitation process, the oxygen impurities and the sintering aid are fully reacted, thereby purifying the lattice structure and improving the thermal conductivity of the material.

[0007] In the present invention, erbium hydride and yttrium oxide are used as composite sintering aids. Erbium hydride decomposes to generate hydrogen and metallic erbium when heated, wherein hydrogen has the function of cleaning the surface of aluminum nitride, thereby improving the sintering activity; metallic erbium generates erbium oxide by replacing aluminum in aluminum oxide. In this process, yttrium oxide and erbium oxide react with aluminum oxide at a certain temperature to generate rare earth aluminates. In addition, since the erbium aluminate generated during the sintering process has a high saturated vapor pressure, under high temperature conditions, the erbium aluminate grain boundary phase is easy to volatilize, reducing the grain boundary phase content, making the contact between aluminum nitride crystals closer, thereby effectively improving the thermal conductivity of the sintered body.

[0008] On the basis of the above technical scheme, preferably, the method comprises the following steps: step 1, weighing the erbium hydride powder of the required mass according to the required ratio of the product and subjecting it to ball milling treatment; step 2, weighing the erbium hydride powder, yttrium oxide powder and aluminum nitride after ball milling and drying treatment according to the required ratio of the product and mixing them thoroughly, and when mixing, weighing the erbium hydride, yttrium oxide and aluminum nitride powder according to the required ratio and placing them in a polytetrafluoroethylene tank, and placing the polytetrafluoroethylene tank on a mixer at 250-300r / min and rotating it for 8-12h to achieve uniform mixing of the powders; step 3, putting the mixed material into a graphite mold, and covering it with boron nitride powder to avoid carburization, and then placing the graphite mold into a hot press furnace in a nitrogen atmosphere for sintering, and obtaining an aluminum nitride ceramic product after sintering.

[0009] More preferably, the erbium hydride powder after ball milling is a chemically pure powder with an average particle size of 3 to 5 μm.

[0010] Further preferably, in step one, erbium hydride powder of the required mass according to the required product ratio is weighed and placed in a polytetrafluoroethylene tank filled with zirconium oxide grinding balls, and ball milled with anhydrous ethanol as the liquid medium. The ball milling time is 4 to 6 hours, the ball mill speed is 250 to 300 r / min, the zirconium oxide grinding balls, erbium hydride powder and anhydrous ethanol are mixed in a mass ratio of 5:1:1 and then ball milled, and the ball-milled powder is vacuum dried in an oven at a drying temperature of 50 to 70°C.

[0011] More preferably, in order to make the sintered body completely dense, the second phase is isolated and evenly distributed at the three-pronged grain boundary, and the grain boundary phase content is reduced, a temperature control strategy is provided in step three, and the temperature change during the sintering process is controlled by the temperature control strategy. The temperature control strategy is to heat to the required temperature at a heating rate of 5-20°C / min at room temperature, and keep warm at this temperature. After the insulation is completed, the temperature is cooled to room temperature with the furnace. The present invention adopts a temperature control strategy to control the temperature change during the sintering process. Since the saturated vapor pressure of erbium aluminate produced during sintering is high, the erbium aluminate grain boundary phase in aluminum nitride at high temperature is easy to volatilize, thereby reducing the grain boundary phase content.

[0012] More preferably, the sintering temperature ranges from 1500 to 1800°C.

[0013] More preferably, the heat preservation sintering time in the temperature control strategy is 2h~6h. Different heat preservation sintering times will affect the density and thermal conductivity of the product.

[0014] More preferably, the sintering pressure in step 3 is 20Mpa~50Mpa. Different sintering pressures will affect the relative density of the product. In addition, it is necessary to pre-press the graphite mold containing the mixed material before sintering, the pre-pressing pressure is 20~40Mpa, and the pre-pressing time is 5~10min.

[0015] More preferably, the aluminum nitride powder in step 2 is a chemically pure powder with an average particle size of 1-2 μm, and the yttrium oxide powder has an average particle size of 1-3 μm.

[0016] On the other hand, the present invention also provides an aluminum nitride ceramic for electronic packaging, which is obtained by sintering using the above-mentioned preparation method of aluminum nitride ceramic for electronic packaging. The obtained product has uniform micromorphology, good density, high thermal conductivity and excellent mechanical properties.

[0017] The aluminum nitride ceramic for electronic packaging and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0018] 1) Effectively improve the thermal conductivity of aluminum nitride ceramics

[0019] By using new rare earth hydrides as sintering aids, the rare earth elements produced during the decomposition of the hydride can combine with the oxygen elements in the alumina, and the generated rare earth oxides can further react with the alumina. Rare earth hydrides have a dual deoxidation effect, effectively preventing oxygen from entering the aluminum nitride lattice and causing defects, thereby significantly improving the thermal conductivity of the material.

[0020] 2) Reduce the content of grain boundary phase

[0021] The saturated vapor pressure of erbium aluminate is relatively high. At high temperatures, the erbium aluminate grain boundary phase in aluminum nitride is easily volatilized, thereby reducing the grain boundary phase content.

[0022] 3) Can effectively improve the density of the sample

[0023] The composite sintering aid can reduce the eutectic line of the aluminate liquid phase, make the liquid phase appear at a lower temperature, and promote the density of the sample.

[0024] In summary, using erbium hydride-yttrium oxide as a sintering aid for aluminum nitride ceramics can significantly reduce the content of grain boundary phase and improve the density and thermal conductivity of the material. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] The present embodiment provides a method for preparing aluminum nitride ceramics for electronic packaging using erbium hydride-yttrium oxide as a composite sintering aid, which specifically includes the following steps: according to product requirements, 10g of erbium hydride powder is quantitatively weighed and placed in a polytetrafluoroethylene tank filled with zirconium oxide grinding balls, and ball-milled for 5 hours with anhydrous ethanol as a liquid medium, and the ball mill speed is 300r / min, wherein the mass ratio of the three is 50g of grinding balls and 10g of anhydrous ethanol; then the ball-milled erbium hydride powder is vacuum dried in an oven; then 0.3g of erbium hydride and 0.3g of yttrium oxide are quantitatively weighed; 29.4g aluminum nitride powder was placed in a polytetrafluoroethylene tank, and it was placed on a mixer with a speed of 300r / min and rotated for 12h to achieve uniform mixing of the powders; the mixed powder was placed in a graphite mold, and covered with boron nitride powder to avoid carburization, and the mixed material in the mold was pre-pressed with a pre-pressing pressure of 30Mpa and a pre-pressing time of 10min, and then the mold was placed in a hot press furnace with a nitrogen atmosphere, and the sintering pressure was 30Mpa. After sintering, aluminum nitride ceramics with uniform micromorphology, good density, high thermal conductivity and excellent mechanical properties were obtained. In order to make the sintered body completely dense and the second phase isolated and evenly distributed at the trifurcated grain boundary, the temperature control strategy was set as follows: heating to 1800℃ at a temperature rise rate of 10℃ / min at room temperature, and sintering at 1800℃ for 4h. After the insulation sintering was completed, the temperature was cooled to room temperature with the furnace to obtain aluminum nitride ceramic products.

[0028] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.28g / cm 3 , the relative density is 98.7%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 162.9W / (m·K).

[0029] Example 2

[0030] Compared with Example 1, this embodiment does not add erbium hydride-yttrium oxide as a composite sintering aid, and sintering aluminum nitride ceramics. Among them, 30g of aluminum nitride powder. The sintering method and sintering conditions are the same as those of Example 1.

[0031] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.19 g / cm 3 , the relative density is 98.0%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 108.6W / (m·K).

[0032] Example 3

[0033] Compared with Example 1, this embodiment only adds yttrium oxide as a sintering aid, and sinters the aluminum nitride ceramic. The sintering method and sintering conditions are the same as those of Example 1. Among them, yttrium oxide powder 0.6g and aluminum nitride powder 29.4g.

[0034] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.28g / cm 3 , the relative density is 98.6%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 142.5W / (m·K).

[0035] Example 4

[0036] Compared with Example 1, this embodiment only adds erbium hydride as a sintering aid and sinters the aluminum nitride ceramic. The sintering method and sintering conditions are the same as those of Example 1. Among them, 0.6g of erbium hydride powder and 29.4g of aluminum nitride powder.

[0037] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.29g / cm 3 , the relative density is 98.7%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 159.4W / (m·K).

[0038] Example 5

[0039] Compared with Example 1, this embodiment quantitatively weighs 0.9 g of erbium hydride, 0.3 g of yttrium oxide and 28.8 g of aluminum nitride powder for sintering. The sintering method and sintering conditions are the same as those of Example 1.

[0040] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.33 g / cm 3 , the relative density is 99.4%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 174.2W / (m·K).

[0041] Example 6

[0042] Compared with Example 1, this embodiment quantitatively weighs 1.5 g of erbium hydride, 0.3 g of yttrium oxide and 28.2 g of aluminum nitride powder for sintering. The sintering method and sintering conditions are the same as those of Example 1.

[0043] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.30g / cm 3 , the relative density is 99.1%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 178.7W / (m·K).

[0044] Example 7

[0045] Example Compared with Example 1, 0.3 g of erbium hydride, 0.9 g of yttrium oxide and 28.8 g of aluminum nitride powder were quantitatively weighed and sintered. The sintering method and sintering conditions were the same as those in Example 1.

[0046] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.33 g / cm 3 , the relative density is 99.3%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 168.8W / (m·K).

[0047] Example 8

[0048] Compared with Example 1, this embodiment quantitatively weighs 0.3 g of erbium hydride, 1.5 g of yttrium oxide and 28.2 g of aluminum nitride powder for sintering. The sintering method and sintering conditions are the same as those of Example 1.

[0049] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.29g / cm 3 , the relative density is 99.0%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 173.3W / (m·K).

[0050] Example 9

[0051] Compared with Example 1, this embodiment quantitatively weighs 0.9 g of erbium hydride, 0.9 g of yttrium oxide and 28.2 g of aluminum nitride powder for sintering. The sintering method and sintering conditions are the same as those of Example 1.

[0052] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.47g / cm 3 , the relative density is 99.8%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 181.1W / (m·K).

[0053] Example 10

[0054] Compared with Example 1, this embodiment quantitatively weighs 1.5 g of erbium hydride, 1.5 g of yttrium oxide and 27 g of aluminum nitride powder for sintering. The sintering method and sintering conditions are the same as those of Example 1.

[0055] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.41g / cm 3 , the relative density is 99.6%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 189.5W / (m·K).

[0056] Embodiment 11

[0057] Compared with Example 1, the temperature control strategy in the sintering step three of this embodiment is set as follows: heating to 1800° C. at 5° C. / min, and sintering at 1800° C. for 4 hours, while other conditions remain unchanged.

[0058] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.33 g / cm 3 , the relative density is 99.3%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 166.5W / (m·K).

[0059] Example 12

[0060] Compared with Example 1, the temperature control strategy in the sintering step three of this embodiment is set to: heating to 1800° C. at 15° C. / min, and sintering at 1800° C. for 4 hours, while other conditions remain unchanged.

[0061] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.26g / cm 3 , the relative density is 98.5%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 156.8W / (m·K).

[0062] Embodiment 13

[0063] Compared with Example 1, the temperature control strategy in the sintering step three of this embodiment is set to: heating to 1800° C. at 20° C. / min, and sintering at 1800° C. for 4 hours, while other conditions remain unchanged.

[0064] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.26g / cm 3 , the relative density is 98.5%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 151.8W / (m·K).

[0065] Embodiment 14

[0066] Compared with Example 1, the temperature control strategy in the sintering step three of this embodiment is set to: heating to 1800° C. at 10° C. / min, and sintering at 1800° C. for 2 h, while other conditions remain unchanged.

[0067] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.26g / cm 3 , the relative density is 98.6%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 160.9W / (m·K).

[0068] Embodiment 15

[0069] Compared with Example 1, the temperature control strategy in the sintering step three of this embodiment is set to: heating to 1800° C. at 10° C. / min, and sintering at 1800° C. for 5 hours, while other conditions remain unchanged.

[0070] The density of the sintered aluminum nitride ceramic product measured by the Archimedes drainage method is 3.30g / cm 3 , the relative density is 99.2%; the thermal diffusion coefficient of the product is measured by laser thermal constant analyzer, and its thermal conductivity is calculated to be 169.2W / (m·K).

[0071] The performance parameters of the samples obtained in Examples 1 to 15 are listed in Table 1 below.

[0072] Table 1

[0073]

[0074] By comparing the performance data of the samples of Examples 1 and 2, it can be found that when sintering aluminum nitride ceramics, the density and thermal conductivity of the sample with erbium hydride and yttrium oxide as composite sintering aids are significantly improved compared with the sample without sintering aids.

[0075] By comparing the sample performance data of Examples 1 and 3, it can be found that when sintering aluminum nitride ceramics, the sample with erbium hydride and yttrium oxide added as a composite sintering aid has higher density and thermal conductivity than the sample with only yttrium oxide added as a sintering aid.

[0076] By comparing the performance data of the samples of Examples 1 and 4, it can be found that when sintering aluminum nitride ceramics, the sample with erbium hydride and yttrium oxide added as a composite sintering aid has a higher density and thermal conductivity than the sample with erbium hydride added as a single sintering aid.

[0077] By comparing the performance data of the samples of Examples 3 and 4, it can be found that the performance of the sample using erbium hydride as a sintering aid is better than that of the sample using yttrium oxide as a sintering aid.

[0078] By comparing the sample performance data of Examples 1, 5 and 6, it can be found that when sintering aluminum nitride ceramics, the thermal conductivity of the sample to which erbium hydride and yttrium oxide are added as composite sintering aids increases with the increase in the amount of erbium hydride added; as the amount of erbium hydride added increases, the density of the sample will be significantly improved in the initial stage, but when the amount of erbium hydride added is too large (for example, reaching 1.5g), the density of the sample will be slightly reduced. The reason for this is analyzed as follows: when the amount of erbium hydride added reaches a certain peak value (for example, 0.9g), the hot pressing sintering method of the present application can make the aluminum nitride, erbium hydride and yttrium oxide particles in the sample fully react, and the particle gaps are greatly eliminated, but when the amount of erbium hydride added continues to increase, the particle gaps of the sample will increase, thereby affecting the density of the sample.

[0079] By comparing the sample performance data of Examples 1, 7 and 8, it can be found that when sintering aluminum nitride ceramics, samples to which erbium hydride and yttrium oxide are added as composite sintering aids, as the amount of yttrium oxide added increases, the performance changes of the samples are similar to those of Examples 1, 5 and 6.

[0080] By comparing the sample performance data of Examples 1, 9 and 10, it can be found that when sintering aluminum nitride ceramics, the samples to which erbium hydride and yttrium oxide are added as composite sintering aids, as the amount of erbium hydride and yttrium oxide added increases simultaneously, the performance changes of the samples are similar to the performance changes of the samples of Examples 1, 5 and 6; but compared with the increase in the amount of one of the components added, the improvement in the thermal conductivity of the samples is more obvious when the amount of erbium hydride and yttrium oxide added increases simultaneously.

[0081] By comparing the sample performance data of Examples 1, 11, 12 and 13, it can be found that when the temperature is controlled during the sintering of aluminum nitride ceramics, the lower the temperature rise rate, the longer the time required to reach the sintering temperature, and the density and thermal conductivity of the sample also increase. The reason for this is that the longer the time required to reach the sintering temperature, the more complete the reaction of the additives in the sample, and therefore the more significant the improvement in sample performance. However, considering the sintering cost, the temperature rise rate is generally controlled at around 10°C / min; when the temperature rise rate is too fast (for example, 20°C / min), the additives in the sample are difficult to fully react, so the thermal conductivity of the sample is relatively low.

[0082] By comparing the sample performance data of Examples 1, 14 and 15, it can be found that when temperature control is performed during the sintering process of aluminum nitride ceramics, as the insulation sintering time is extended, the density and thermal conductivity of the sample will also increase accordingly; but after the insulation sintering time exceeds 4 hours, the changes in its density and thermal conductivity slow down.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing aluminum nitride ceramics for electronic packaging, characterized in that: In the sintering process of aluminum nitride ceramics, aluminum nitride is used as raw material, and erbium hydride and yttrium oxide are added as composite additives for sintering. The preparation method comprises the following steps: Step 1, weighing the erbium hydride powder of the required mass according to the product demand ratio and ball milling the erbium hydride powder, wherein the erbium hydride powder after ball milling is a chemically pure powder with an average particle size of 3-5 μm; Step 2: Weigh the erbium hydride powder, yttrium oxide powder and aluminum nitride that have been ball-milled and dried according to the required ratio of the product and mix them thoroughly; the average particle size of the aluminum nitride powder is 1-2 μm, and the average particle size of the yttrium oxide powder is 1-3 μm; Step three, putting the mixed material into a graphite mold, and putting the graphite mold into a hot pressing furnace in a nitrogen atmosphere for sintering, and obtaining an aluminum nitride ceramic product after sintering; a temperature control strategy is provided during the sintering process, and the temperature change during the sintering process is controlled by the temperature control strategy, and the temperature control strategy is to heat to the required temperature at a heating rate of 5-20°C / min at room temperature, and keep warm at this temperature, and after the insulation is completed, cool down to room temperature with the furnace; the required sintering temperature range is 1500-1800°C; the insulation sintering time in the temperature control strategy is 2h-6h; the sintering pressure is 20Mpa-50Mpa; The erbium hydride powder and the yttrium oxide powder are both 3wt% to 5wt% of the total mass of the mixed materials required for sintering.

2. The method for preparing an aluminum nitride ceramic for electronic packaging according to claim 1, characterized in that: In the step 1, the erbium hydride powder of the required mass according to the product demand ratio is weighed and placed in a polytetrafluoroethylene tank filled with zirconium oxide grinding balls, and ball milling is performed using anhydrous ethanol as a liquid medium. The zirconium oxide grinding balls, erbium hydride powder and anhydrous ethanol are mixed in a mass ratio of 5:1:1 and then ball milling is performed.

3. An aluminum nitride ceramic for electronic packaging, characterized in that: The aluminum nitride ceramic for electronic packaging is sintered using the preparation method of claim 1 or 2.

Citation Information

Patent Citations

  • Low-temperature sintering preparation method of AlN ceramic added with multi-element sintering aid

    CN104230344A

  • Manufacturing method of heating assembly, heating device and heating smoking set

    CN115956720A

Cited By

  • High-thermal-conductivity black aluminum nitride ceramic substrate and preparation method and application thereof

    CN122608426A